Why do foreign-owned firms pay more? The role of on-the-job training - Holger Görg; Eric Strobl; Frank A. Walsh (Centre for Economic Policy Research (CEPR), 2007)
While foreign-owned firms have consistently been found to pay higher wages than domestic firms to what appear to be equally productive workers, the causes of this remain unresolved. In a two-period bargaining framework we show that if training is more productive and specific in foreign firms, foreign firm workers will have a steeper wage profile and thus acquire a premium over time. Using a rich employer-employee matched data set we verify that the foreign wage premium is only acquired by workers over time spent in the firm and only by those that receive on the job training, thus providing empirical support for a firm specific human capital acquisition explanation.
Keywords: F23; J24; 330; Lohnniveau; Eigentümerstruktur; Multinationales Unternehmen; Berufsbegleitende Ausbildung; Verarbeitendes Gewerbe; Ghana